(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Background: The prevalence of anaemia in general and iron deficiency anaemia in particular is presently rising in the society. The primary objective of this study was to determine the prevalence of anaemia among school going children in rural and semi urban areas of Kangra district (Himachal Pradesh). Secondary objective was to identify the etiological and contributory factors in anaemia on the basis of Ayurvedic fundamentals. Methods: A population of 200 children studying in different schools of rural and semi urban areas of Kangra district Himachal Pradesh and IPD as well as OPD of department of Kaumarbhritya, R.G.G. P.G. Ayurvedic college and hospital Paprola were included in the survey. The data obtained from the survey was evaluated to assess the prevalence of anemia and its correlates. To fulfill the aims and objectives a specially prepared performa was designed and all details of the children were recorded in it. Results: The prevalence of anaemia was found to be 69% in school going children in rural areas of Kangra district, Himachal Pradesh. The major risk factors which were observed in present study were nutrition, socio-economic status, pica and dewormification. Conclusion: Anaemia is comparatively more common among children of semi urban and rural areas of Himachal Pradesh possible due to multiple factors like low socioeconomic status, menstruation and inadequate diet etc.